2014
DOI: 10.1371/journal.pone.0091641
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Improvements of Spatial Learning and Memory Abilities in Chronic Rotenone Intoxicated Mice

Abstract: The liposoluble insecticide rotenone is commonly used as a mitochondrial complex I inhibitor to replicate Parkinson's disease (PD) pathological features. However, there was no assessment of the spatial learning and memory abilities in chronic rotenone-induced PD models. In the present study, by rotarod test and Thioflavine T staining, we first noted the impairment of motor coordination in rotenone-treated group for 3 months, as well as alpha-synuclein inclusions in the nigral dopaminergic neurons in C57BL/6 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…Cognitive decline 472 Cognition was shown to be altered in rotenone-treated rats as 473 transfer latency in the elevated plus-maze learning task was 474 prolonged in comparison to controls; the detected high levels of 475 acetylcholinesterase activity was subsequently proposed to be a 476 possible contributor to this cognitive decline (Kaur et al, 2011).477 Memory impairment has also been reported in rotenone-treated 478 rats as they failed to detect the novel object with equal time spent 479 with the familiar and novel object in the object recognition test 480 (DosSantos et al, 2013). A recent study similarly reported a defect 481 in spatial memory in mice treated with rotenone at 5 mg/kg 482 intragastrically 5 days a week for 1 month(Jia et al, 2014). 483 Remarkably when this dosing paradigm was extended to 3 months 484 the rotenone mice had improved spatial learning and memory(Jia 485 et al, 2014), highlighting the need for further investigation to 486 understand the pathophysiology behind these findings.487 2.3.5.…”
mentioning
confidence: 99%
“…Cognitive decline 472 Cognition was shown to be altered in rotenone-treated rats as 473 transfer latency in the elevated plus-maze learning task was 474 prolonged in comparison to controls; the detected high levels of 475 acetylcholinesterase activity was subsequently proposed to be a 476 possible contributor to this cognitive decline (Kaur et al, 2011).477 Memory impairment has also been reported in rotenone-treated 478 rats as they failed to detect the novel object with equal time spent 479 with the familiar and novel object in the object recognition test 480 (DosSantos et al, 2013). A recent study similarly reported a defect 481 in spatial memory in mice treated with rotenone at 5 mg/kg 482 intragastrically 5 days a week for 1 month(Jia et al, 2014). 483 Remarkably when this dosing paradigm was extended to 3 months 484 the rotenone mice had improved spatial learning and memory(Jia 485 et al, 2014), highlighting the need for further investigation to 486 understand the pathophysiology behind these findings.487 2.3.5.…”
mentioning
confidence: 99%
“…For mice, the concentration range used for intragastric rotenone administration is 0.25 mg/kg (min) to 50 mg/kg (max), and the concentration used is dependent on the exposure duration. For the exposure duration of 14-28 days, higher concentrations (30-50 mg/kg) were used (Chiu et al, 2015;Inden et al, 2007;Takeuchi et al, 2009), whereas 5 mg/kg was used for longer exposure up to 3 months (Jia et al, 2014;Pan-Montojo et al, 2010).…”
Section: Supporting Publications 2016: En-955 69mentioning
confidence: 99%
“…Other frequently-reported key intermediate events include decrease in glutathione (Hosamani & Muralidhara, 2009;Sanchez-Reus et al, 2007;Saravanan et al, 2005;Swarnkar et al, 2010;Xiong et al, 2009b) or dopamine levels (Abdin & Hamouda, 2008;Alam & Schmidt, 2002;He et al, 2003;Hosamani & Muralidhara, 2009;Inden et al, 2007;Ling et al, 2004b;Milusheva et al, 2005;Monti et al, 2010;Saravanan et al, 2005;Sindhu et al, 2005;Xiong et al, 2009b), altered dopamine metabolism (Antkiewicz-Michaluk et al, 2003;Antkiewicz-Michaluk et al, 2004;Ling et al, 2004b;Monti et al, 2010;Santiago et al, 2010), increased oxidative stress such as increased ROS/peroxynitrite production Hosamani & Muralidhara, 2009;Panov et al, 2005;Saravanan et al, 2005) and lipid peroxidation (Bashkatova et al, 2004;Betarbet et al, 2006;Chiu et al, 2015;Hosamani & Muralidhara, 2009;Inden et al, 2007;Jia et al, 2014;Monti et al, 2010;PanMontojo et al, 2010;Sanchez-Reus et al, 2007;Sherer et al, 2003b;Swarnkar et al, 2010;Wu et al, 2015;Xiong et al, 2009b), altered neurite formation (Esteve-Rudd et al, 2011;Fan et al, 2011;…”
Section: Supporting Publications 2016: En-955 70mentioning
confidence: 99%
See 2 more Smart Citations